Organic synthesis : state of the art 2009-2011 - Taber, D. F. (Douglass F.), 1948- (Oxford University Press, 2013)
Organic synthesis is a vibrant and rapidly evolving field; we can now cyclize amines directly onto alkenes. Like its predecessors, this reference leads readers quickly to the field's more important recent developments. Two years of Douglass F. Taber's popular weekly online column, ""Organic Chemistry Highlights"", as featured on the organic-chemistry.org website, are consolidated here, with cumulative indices of all four volumes in this series. Important topics that are covered range from powerful new methods for C-C bond construction to asymmetric organocatalysis and direct C-H functionalizat.